Short stature is an inflammatory disadvantage among middle-aged Japanese men. Issue 5 (September 2016) - Shimizu, Yuji; Yoshimine, Hiroyuki; Nagayoshi, Mako; Kadota, Koichiro; Takahashi, Kensuke; Izumino, Kiyohiro; Inoue, Kenichiro; Maeda, Takahiro
Abstract Objectives A positive association between white blood cell count and carotid atherosclerosis has been reported. Our previous study also found an inverse association between height and carotid atherosclerosis in overweight but not non-overweight men. However, no studies have reported on the association between high white blood cell (WBC) count and height accounting for body mass index (BMI) status. Methods We conducted a hospital-based general population cross-sectional study of 3016 Japanese men aged 30–59 years undergoing general health check-ups between April 2013 and March 2014. High WBC count was defined as the highest tertiles of WBC count among total subjects. Results Independent of classical cardiovascular risk factors, height was found to be inversely associated with high WBC count, especially for subjects with a BMI ≥ 23 kg/m2 . The classical cardiovascular risk factors adjusted odds ratios (ORs) and 95 % confidence intervals (CIs) of high WBC count for an increment of one standard deviation (SD) in height (5.7 cm) were 0.91 (0.83–0.99) for total subjects, 1.00 (0.86–1.15) for subjects with a BMI < 23 kg/m2 and 0.86 (0.77–0.96) for subjects with a BMI ≥ 23 kg/m2 . Conclusion Independent of classical cardiovascular risk factors, height was found to be inversely associated with high WBC count, especially for those with a BMI ≥ 23 kg/m2 . Compared to high stature, short stature appears to convey an inflammatory disadvantage among Japanese men, especially those with a BMI ≥ 23 kg/m2 .